Predicting the Willingness and Purchase of Travel Insurance During the COVID-19 Pandemic - Al Mamun, Abdullah; Rahman, Muhammad Khalilur; Yang, Qing; Jannat, Taslima; Salameh, Anas A.; Fazal, Syed Ali (Frontiers in Public Health, 2022)
This study explored the willingness and purchase of travel insurance during the COVID-19 pandemic amongst working adults to ensure their safety and welfare through the lens of the theory of planned behaviour. Primary data gathered from 1118 working adults across Malaysia, and analysed using partial least squares structural equation modelling. The study outcomes revealed that attitude towards travel insurance were significantly influenced by insurance literacy, perceived health risk, and health consciousness. The willingness of working adults to purchase travel insurance was highly influenced by attitude, subjective norm, and perceived behavioural control, but unaffected by perceived product risk. The purchase of travel insurance was positively influenced by willingness to purchase travel insurance. Apparently, travel insurance literacy and perceived health risk should be emphasised amongst working adults to encourage them to purchase travel insurance policies for travel abroad.